The Shared Mission: A Phenomenological Study on the Marist-Lay Partnership - Friales, Wilter (JPAIR Multidisciplinary Research, 2019)
The term partnership is being viewed in the context that the lay people are not just simply workers or employees of the Brothers in schools, but they are partners in fulfilling the mission of education. This Phenomenological Study of the Marist-lay partnership explored the lived experiences of both the Marist lay and Marist Brothers in the context of a partnership for the mission of the Marist. It is a phenomenological qualitative design of research that aimed to explore the lived experiences of both the Marist Brothers and the Lay in the context of the partnership. This qualitative research used the transcendental Phenomenological approach following the method introduced by Moustaka (1994). The first part of the study explored the lived experiences of the Marist Brothers and lay while they work with the Marist mission. It presented their vocation stories, challenges encountered, and attitudes towards work, working relationships, and the impact of such a partnership in their lives. The second part of the study revealed the different meanings and the themes drawn in understanding the concept of Marist-lay partnership as perceived by the Marist Brothers and the lay in working for the Marist mission. The emergent themes were extracted after the thorough process of thematic coding, analysis, and categorization of the transcripts from the in-depth interview of the researcher to the identified participants of the study. Based on the result of the exploration, it was drawn out that collaboration appeared to be very important to be established in the Marist community.
Keywords: Education; Marist-Lay Partnership; Phenomenological Qualitative Research design; Philippines